POST OPERATIVE COMPLICATIONS OF PARTIAL NEPHRECTOMY WITH RESPECT TO TUMOR LOCATION - Muhammad Shahzad; Nasir Jamil, Muhammad; Hamza Ashraf; Raja Asim Shafique; Muhammad Faridullah Thaimur; Ehsan ul Islam (Journal of Ayub Medical College Abbottabad, 2023)
Background: Partial Nephrectomy has been the go-to approach for the treatment of small sized renal tumours for years now. Like any other surgical procedure, it is associated with post-operative complications. The study was aimed at determining the post-operative complications of open partial nephrectomy with respect to tumour location. Methods: This descriptive cross-sectional study was done on 45 patients as per inclusion criteria. The patients were managed as per department protocols and were observed for the development of immediate post-operative complications during hospital stays. RESULTS: Post-operative complications were observed in 4 (8.9%) patients and included haemorrhage (n=1; 2.2%) and urine leak (n=3; 6.7%). There was a statistically significant association between post-operative complications of partial nephrectomy and central tumour location (p=0.008, OR=14.52 and LR=5.70) and increased age (p=0.04, LR=5.40 and OR=8.90). Discussion: Increased age and tumour location may play a significant role in determining the likelihood of post-operative complications in patients who have undergone surgery for renal tumours.